Investigating AbdulHamid AbuSulayman view on the concept of freedom based on his "crisis in the Muslim mind" - Shehu, Fatmir Mehdi (International Institute for Muslim Unity (IIMU), 2024)
This chapter seeks to investigate the views of the prominent Muslim scholar and thinker, AbdulHamid AbuSulayman, on the concept of “Freedom” based on his masterpiece “Crisis in the Muslim Mind”. Its goal is to identify selected texts related to AbuSulayman’s main views on “Freedom” and its dimensions of Belief, Islamic Thought, and Social Behavior, and further, extract and analyze his views as well as evaluate them if necessary. The main discussion presented in this chapter is divided into two parts. The first part includes a brief description of AbdulHamid AbuSulayman’s intellectual development and his work “Crisis in the Muslim Mind.” The second part analyzes the notion of “Freedom” emphasizing his views on the definition and characteristics of freedom, as well as its relationship with the three main features of Belief, Islamic Thought, and Social Behavior. New insights into the concept of “Freedom” are presented in this chapter as a result of investigating the viewpoint of AbdulHamid AbuSulayman.